Mechanisms of hormonal regulation of the peripheral circadian clock in the colon - Polidarová, Lenka; Houdek, Pavel; Sládek, Martin; Novosadová, Zuzana; Pácha, Jiří; Sumová, Alena (Chronobiology international, 2017)
Colonic function is controlled by an endogenous clock that allows the colon to optimize its function on the daytime basis. For the first time, this study provided evidence that the clock is synchronized by rhythmic hormonal signals. In rat colon, adrenalectomy decreased and repeated applications of dexamethasone selectively rescued circadian rhythm in the expression of the clock gene Per1. Dexamethasone entrained the colonic clock in explants from mPer2Luc mice in vitro. In contrast, pinealectomy had no effect on the rat colonic clock, and repeated melatonin injections were not able to rescue the clock in animals maintained in constant light. Additionally, melatonin did not entrain the clock in colonic explants from mPer2Luc mice in vitro. However, melatonin affected rhythmic regulation of Nr1d1 gene expression in vivo. The findings provide novel insight into possible beneficial effects of glucocorticoids in the treatment of digestive tract-related diseases, greatly exceeding their anti-inflammatory action.
Keywords: Circadian clock; colon; kolon; regulace genové exprese; nadledviny; entrainment; mutace; fotoperioda; krysa rodu Rattus; Colon; zvířata; myši; potkani Wistar; Mice; Circadian Clocks; Gene Expression Regulation; Rats, Wistar; Adrenal Glands; epifýza mozková; Photoperiod; Rats; Mice, Inbred Strains; cirkadiánní hodiny; Animals; Mutation; inbrední kmeny myší; Pineal Gland; cirkadiánní proteiny Period; Period Circadian Proteins